Investigating the use of alumina (Al2O3) to substitute magnesia (MgO) in capsule components for diamond synthesis in high pressure high temperature (HPHT) process - Mazula, Maqhawe (My University, 2020)
The research work described in this dissertation concerns an investigation into the feasibility of replacing magnesia with alumina, as a seedpad material for diamond synthesis from diamond seeds, in the high pressure high temperature 5 GPa, 1450 oC, (HPHT) cubic press. A seedpad is a magnesia ceramic disc with diamond seeds crystals embedded at defined orientation and spacing onto a disc. Seedpad purity is critical to prevent contaminating or destabilising HPHT diamond synthesis. The supplied commercial magnesia grade used by Element Six Pty Ltd for seedpads manufacture, Nedmag has a purity of 98.5 % MgO, the remainder accounts for impurities like CaO, B2O3 and SiO2. MgO and CaO have the ability to absorb atmospheric moisture to form hydroxides, B2O3 and SiO2 may contaminate diamond synthesis by forming inclusions in the crystalline lattice. Magnesia seedpads are pre-treated in the 1140 oC vacuum furnace to decompose moisture and impurities, and stored in a nitrogen cabinet to prevent moisture re-absorption. Alternative seedpad material not susceptible to moisture absorption, of higher purity than Nedmag, able to make seedpads with sufficient strength comparable to magnesia seedpads was investigated. Spray dried alumina, spray dried from KSM99, a high grade alumina powder sourced from Albemarle GmbH, Germany, was found to be a possible alternative powder for making higher purity alumina seedpad with a sufficient strength comparable to magnesia seedpad. The moisture test conducted proves magnesia (Nedmag) has a greater moisture absorption than alumina (KSM99) in ambient air. The spray dried magnesia and alumina powders were fully characterised, uniaxial compacted and fired to specific seedpad compacts density. A test to compare compressive fracture strength for both materials was done on an Instron mechanical test apparatus on cylindrical magnesia and alumina compacts, alumina compacts showed the mechanical strength required for seedpads manufacture. Graphite with metal solvents (GMS) prepared using Element Six Pty Ltd method, were used as a carbon source for diamond synthesis in the HPHT cubic press. The stability of magnesia and alumina in the presence of (GMS) at HPHT diamond synthesis condition shows suitability for both ceramics to be used as seedpads. The diamond crystals synthesised from magnesia seedpads and alumina seedpads were of similar colour and morphology.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering.